2019
DOI: 10.1007/s00125-019-4872-7
|View full text |Cite
|
Sign up to set email alerts
|

Metformin increases endogenous glucose production in non-diabetic individuals and individuals with recent-onset type 2 diabetes

Abstract: Aims/hypothesis Metformin is the endorsed first-line glucose-lowering drug for treating patients with type 2 diabetes but despite more than 50 years of use, no consensus has been reached on its mechanisms of action. In this study, we investigated the glucoselowering effects of metformin in individuals with type 2 diabetes and non-diabetic individuals. Methods We performed a randomised, placebo-controlled trial in 24 individuals with recent-onset type 2 diabetes (diabetes duration 50 [48] months) who had good g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
46
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(57 citation statements)
references
References 13 publications
9
46
2
Order By: Relevance
“…In keeping with this, they show an increase in their fasting EGP, which may be due to glucagon-induced glycogenolysis or gluconeogenesis. This finding is consistent with the data presented by Gormsen et al [6].…”
supporting
confidence: 94%
See 1 more Smart Citation
“…In keeping with this, they show an increase in their fasting EGP, which may be due to glucagon-induced glycogenolysis or gluconeogenesis. This finding is consistent with the data presented by Gormsen et al [6].…”
supporting
confidence: 94%
“…It is, therefore, with great interest that we read the article recently published in Diabetologia entitled 'Metformin increases endogenous glucose production in non-diabetic individuals and individuals with recent-onset type 2 diabetes' [6]. In the article, using studies of whole-body glucose metabolism, including non-steady state glucose tracer kinetics and hyperinsulinaemic-euglycaemic clamping, Gormsen et al report that metformin treatment is associated with an increase in the glucose rate of disappearance (R d ), glucagon levels and EGP both in healthy control individuals and in individuals with recent-onset type 2 diabetes with good glycaemic control.…”
mentioning
confidence: 99%
“…Type 2 diabetes is commonly associated with nutrient excess which predicts compromised intracellular homeostasis. Recent studies have reported lack of efficacy of metformin in healthy non-diabetic people as well as in newly diagnosed well-controlled type 2 diabetes [116,117]. Although several factors may interact with the efficacy of metformin on endogenous glucose production, further work on the metformin mechanism should focus on cell and animal models with compromised intracellular metabolite homeostasis that more closely simulate the dysregulation in poorly controlled type 2 diabetes, to determine whether AMPK-independent repression of G6pc by metformin predominates in the compromised metabolic state.…”
Section: Perspectivesmentioning
confidence: 99%
“…To date, metabolomics-based approaches have become increasingly applied to all aspects of diabetes research. Recent literature shows that metabolomics has been applied to biomarker and drug discovery, drug assessment [259, 260], toxicology [261, 262], and clinical biochemistry with a particular focus on gestational diabetes mellitus (GDM) [263270]. Some of the recent metabolomics-aided discoveries in antidiabetic plant research are summarised below.…”
Section: Metabolite Profilingmentioning
confidence: 99%
“…For instance, a metabolomics-based study found that 90 days of treatment with metformin increased endogenous glucose production in newly diagnosed T2DM patients. This challenges the widely accepted paradigm that the antihyperglycaemic effects of metformin is primarily due to inhibition of endogenous glucose production in the liver [260]. This illustrates the importance of establishing the metabolic effects of drugs and determining whether the same drug may differ in their mechanisms of action within different stages of a disease.…”
Section: Metabolite Profilingmentioning
confidence: 99%